Uporaba prekatnih evociranih potencialov pri bolnikih po transplantaciji srca - Vrtovec, Bojan (Zdravniški vestnik, 2005)
Background. Adequate detection and treatment of acute allograft rejection is one of the most important predictors of post-transplant survival of cardiac transplant recipients. Recently, a number of novel, non-invasive tools have allowed for earlier detection and better treatment of rejection episodes. Methods. Using the signal from a special pacemaker implanted during the transplant procedure, the intraventricular electrograms can be obtained. The amplitude and the conduction time of the intraventricular electrogram provide information on electrophysiological properties of ventricular myocardium. Due to edema and inflammation during acute rejection, the amplitude of the signal decreases and the conduction time is prolonged. Results. In Ljub jana Medical Center Transplarctation Programme the measurement of intramyocardial electrograms has been shown to represent a reproducible and reliable methodology which led to fewer cardiac biopsy procedures and earlier and better treatment of cardiac allograft rejection. Conclusions. The analysis of intramyocardial electrograms is an important non-invasive tool which allows for better follow-up of cardiac transplant recipients and earlier detection and treatment of allograft rejection episodes.
Keywords: Cardiac Pacing, Artificial; Electrocardiography; Elektrokardiografija; Graft Rejection; Heart Transplantation; Heart Ventricle; Srce, presaditev; Srčni prekat; Srčno vzpodbujanje, umetno; Vsadek, zavrnitev